Dynamics of ring-based CVGs including non-linear geometrical effects - Di Napoli, Violetta (2021)
Micro-Electro-Mechanical System (MEMS) ring-based Coriolis Vibrating Gyroscopes (CVGs) are devices that use vibration of micro-engineered thin rings to sense the angular rate of moving objects. High performance ring-based CVGs used in inertial navigation applications need to ensure the achievement of high sensitivity and improved signal-to-noise ratio. To achieve improved signal-to-noise ratio, ring-based resonators are designed to ensure low damping and mode-matching between drive and sense modes of vibration, and sensor sensitivity is improved by exciting the drive mode into large amplitude vibration. Large amplitude drive responses can cause the resonator to operate in a regime where geometrical non-linearity effects (i.e. non-linear strain-displacement relations) arise which have potential to alter sensor performance compared to a linear resonator operating at small amplitudes of vibration.